Development of 2D materials composite film - Lin, Zhide (Nanyang Technological University, 2021)
Research and development of two-dimensional materials such as MXene made great progress due to its various unique properties which leads to the discovery of a plethora of application in coatings, filtrations, energy storage applications, and electromagnetic shielding. To realize its potential applications, MXene must be made into film from bulk MXene powder. In this project, experiments were conducted to assemble MXene into film through exfoliation, vacuum assisted filtration and solution casting. More specifically, dispersibility of MXene in water through liquid-exfoliation was improved for the best performing solvent, before assembly of 2D few-layer MXene into films with the exfoliated solutions was performed. The aim is to support the investigation in potential applications of MXene films stacking into an electronic magnetic wave shielding structure known as Dallenbach Layer. Herein, the MXene and other 2D materials were mixed with Binding materials such as PVDF and PVA. The ideal binding material was chosen based on its ability to film up and the best ratio of MXene: binder was established through a series of experiments. Overall procedure of film making was optimized by testing and using the chosen solvent, binding material, and their ratio. MXene-binder composite films were created, stacked into Dallenbach Layers and would be tested for their electromagnetic interference shielding capabilities in future projects.